Raw lacquer acrylic resin composite material, preparation method and application
By using the interpenetrating network structure of raw lacquer and acrylic resin, the problem of the reaction rate of raw lacquer being affected by temperature and humidity is solved, thereby improving its application range and performance, and forming a new composite material that combines the advantages of both raw lacquer and acrylic resin.
Patent Information
- Application Number
- CN202511046413.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-29
- Publication Date
- 2025-11-28
AI Technical Summary
The reaction rate of raw lacquer is greatly affected by temperature and humidity, leading to application bottlenecks. In addition, the limited color of traditional raw lacquer restricts its application in many fields.
A raw lacquer-acrylic composite material is prepared by esterification and addition reactions of raw lacquer and acrylic resin to form an interpenetrating network structure. The acrylic resin is then modified with epoxy, polyurethane, and silicone to improve its permeability and adhesion.
It achieves rapid drying, light color, and strong weather resistance of raw lacquer, expanding its application in fields such as cultural relic protection, furniture, lacquerware manufacturing, architectural decoration, and high-performance adhesives, reducing dependence on fossil materials and meeting environmental protection standards.
Smart Images

Figure CN121022264A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of new bio-based materials of raw lacquer and its preparation, in particular to a raw lacquer acrylic resin composite material, a preparation method and an application. The new grafted raw lacquer composite material overcomes the bottleneck problems of raw lacquer brushing, drying and color depth, has the material properties of raw lacquer and acrylic resin, and has excellent performance such as fast drying, sprayability, light color, and strong weather resistance. BACKGROUND
[0002] Raw lacquer is a milky white viscous liquid cut from lacquer trees, has strong penetration, excellent durability and corrosion resistance, and has a long application history in the fields of cultural relics, furniture and lacquerware manufacturing. Raw lacquer is a water-in-oil emulsion structure, relies on lacase catalysis and oxidation polymerization, and its biological crosslinking polymerization process is greatly affected by temperature and humidity, which has also become a bottleneck problem in the application of raw lacquer. Acrylic resin is a synthetic polymer material, has excellent performance such as fast drying speed, good film forming property, yellowing resistance and good flexibility, and is widely used in the industries of coatings and adhesives. The esterification and addition reaction of phenolic hydroxyl groups in raw lacquer and ester groups in acrylic resin occurs, forming a network structure of lacquer and acrylic molecules, synthesizing a new grafted raw lacquer acrylic composite material, solving the problem of raw lacquer reaction rate, improving the penetration and bonding performance, and expanding the new application direction. SUMMARY
[0003] In order to adapt to the industrial development needs of new era and new technology, break through the application bottleneck and field problem of raw lacquer, the purpose of the present application is to provide a raw lacquer acrylic resin composite material, a preparation method and an application based on the excellent performance of raw lacquer, expand the industrial development direction, and extend the industrial chain.
[0004] In order to achieve the above-mentioned task, the technical scheme adopted by the present application is:
[0005] A raw lacquer acrylic composite material, by mass percentage, the composite material comprises: 5-30% of raw lacquer or lacquer, 1-2% of catalyst, 1-10% of aldehyde substance, 10-20% of crosslinking agent, 10-30% of acrylic resin, 25-70% of solvent and 1-5% of thickening agent; the sum of the percentages of the above-mentioned raw materials is 100%; the acrylic resin is selected from at least one of epoxy modified acrylic resin, polyurethane modified acrylic resin, silicone modified acrylic resin and water-based acrylic resin.
[0006] The molecular weight of the epoxy modified acrylic resin, the polyurethane modified acrylic resin and the silicone modified acrylic resin is 5000-10000, 30000-50000 and 20000-50000 respectively.
[0007] Optionally, the acrylic resin is water-based acrylic resin, the molecular weight is 80000-100000, and the raw lacquer is refined raw lacquer; the composite material comprises 5-30% of refined raw lacquer, 10-20% of cross-linking agent, 10-30% of water-based acrylic resin, 25-70% of solvent, and 1-5% of thickening agent, and the sum of the percentages of the above raw materials is 100%.
[0008] Optionally, the percentage of the decoction disc of the raw lacquer is more than 60%, and the urushiol content is more than 50%.
[0009] Optionally, the raw lacquer is refined raw lacquer, the percentage of the decoction disc of the refined raw lacquer is more than 90%, and the urushiol content is more than 50%.
[0010] Optionally, the cross-linking agent is at least one of epoxy resin, boiled tung oil and phthalic anhydride; the thickening agent is at least one of hydroxymethyl cellulose modified acrylic copolymer, bentonite, polyamide wax and hydrogenated castor oil; and the solvent is at least one of acetone, butanone, ethanol, ethyl acetate and dimethylbenzene.
[0011] Optionally, the catalyst is at least one of ammonia water, ethylenediamine, sodium hydroxide, triethanolamine, benzoyl peroxide, di-tert-butyl peroxide and methyl ethyl ketone peroxide; and the aldehyde substance is at least one of formaldehyde, furfural, n-butyraldehyde and amyl butyraldehyde.
[0012] The synthesis method of the raw lacquer acrylic composite material according to any one of the present application comprises the following steps:
[0013] The raw lacquer or urushiol, the aldehyde substance, the catalyst and the solvent are mixed at normal temperature according to the formula amount, the polymerization reaction is carried out at 60-80 DEG C for 0.1-4 hours, the temperature is raised to 138 DEG C for dehydration, the temperature is lowered to room temperature, the acrylic resin and the cross-linking agent are added and reacted for 0.1-0.5 hours, the thickening agent is added under stirring for 0.1-0.5 hours, and the raw lacquer acrylic composite material is obtained.
[0014] The synthesis method of the raw lacquer acrylic composite material according to any one of the present application comprises the following steps:
[0015] Optionally, the heating rate during the mixing is 5 DEG C / min, and the flow rate of the nitrogen gas is 5-10 mL / min.
[0016] The raw lacquer acrylic composite material according to any one of the present application is used for preparing functional coating.
[0017] The present application has the following beneficial effects:
[0018] 1. Performance advantage: The raw lacquer acrylic resin composite prepared by the present application not only retains the corrosion resistance and durability advantages of raw lacquer, but also solves the problems of poor UV resistance and single color (traditional raw lacquer is mostly brown-black) of raw lacquer through the introduction of acrylic resin, while improving the flexibility and impact resistance of the coating, and has a wide range of applications. It is a green new material with excellent performance.
[0019] 2. Environmental protection: The raw lacquer acrylic resin of the present application uses the natural components of raw lacquer to reduce the use of acrylic resin, while reducing the allergenicity of raw lacquer materials and reducing dependence on fossil materials, which is more in line with the environmental protection standards of the modern coating industry.
[0020] 3. Wide application: The bio-based resin of the present application has excellent material performance and low cost, and breaks through the limitation of single color of traditional raw lacquer, and is suitable for more fields such as cultural relic protection and restoration, furniture, lacquerware manufacturing, building decoration, high-performance adhesive, handicrafts, etc. BRIEF DESCRIPTION OF DRAWINGS
[0021] The accompanying drawings are included to provide a further understanding of the present disclosure, and constitute a part of the specification, and together with the following detailed description, serve to explain the present disclosure, but do not constitute a limitation on the present disclosure. In the drawings:
[0022] Figure 1 is an infrared spectrum of acrylic resin;
[0023] Figure 2 is an infrared spectrum of raw lacquer;
[0024] Figure 3 is an infrared spectrum of raw lacquer acrylic resin of the present application;
[0025] Figure 4 is a scanning electron microscope surface morphology graph (left) and cross-section morphology graph (right) of raw lacquer;
[0026] Figure 5 is a scanning electron microscope surface morphology graph (left) and cross-section morphology graph (right) of raw lacquer acrylic resin of the present application. DETAILED DESCRIPTION
[0027] In order to make the purpose, content and advantages of the present application clearer, the specific embodiments of the present application are described in further detail below in combination with the drawings and examples.
[0028] The lacquer acrylic composite material of the present application comprises, in percentage by mass, 5-30% of raw lacquer or urushiol, 1-2% of catalyst, 1-10% of aldehyde substance, 10-20% of cross-linking agent, 10-30% of acrylic resin, 25-70% of solvent, and 1-5% of thickening agent, with the sum of the percentages of the above-mentioned raw materials being 100%; the acrylic resin is selected from at least one of epoxy-modified acrylic resin, polyurethane-modified acrylic resin, silicone-modified acrylic resin and water-based acrylic resin; the molecular weight of the epoxy-modified acrylic resin, polyurethane-modified acrylic resin and silicone-modified acrylic resin is 5000-10000, 30000-50000 and 20000-50000 respectively.
[0029] In the present application, the acrylic resin is water-based acrylic resin with a molecular weight of 80000-100000, and the raw lacquer is refined raw lacquer; the composite material comprises 5-30% of refined raw lacquer, 10-20% of cross-linking agent, 10-30% of water-based acrylic resin, 25-70% of solvent and 1-5% of thickening agent, with the sum of the percentages of the above-mentioned raw materials being 100%.
[0030] In the present application, the acrylic resin is a polymer copolymerized from monomers such as methacrylate, acrylate and methacrylic acid in different proportions; the epoxy-modified acrylic resin is obtained by reacting epoxy resin with the active groups of acrylic resin; the polyurethane-modified acrylic resin is aromatic polyurethane acrylate or aliphatic polyurethane acrylate; and the water-based acrylic resin is water-based acrylic emulsion or dispersion.
[0031] In the present application, the decoction disc fraction of the raw lacquer is more than 60%, and the urushiol content is more than 50%.
[0032] In the present application, the raw lacquer can be refined raw lacquer, the decoction disc fraction of the refined raw lacquer is more than 90%, and the urushiol content is more than 50%.
[0033] In the present application, the aldehyde substance is aldehyde substance such as formaldehyde, furfural, n-butyl aldehyde and amyl butyl aldehyde.
[0034] In the present application, the cross-linking agent is one of epoxy resin, boiled tung oil and phthalic anhydride.
[0035] In the present application, the catalyst is one of ammonia water, ethylenediamine, sodium hydroxide, triethanolamine, benzoyl peroxide, di-tert-butyl peroxide and methyl ethyl ketone peroxide.
[0036] In the present application, the thickening agent is at least one of hydroxymethyl cellulose modified acrylic copolymer, bentonite, polyamide wax and hydrogenated castor oil.
[0037] In the present application, the solvent is at least one of acetone, butanone, ethanol, ethyl acetate and dimethylbenzene.
[0038] The synthesis method of the lacquer acrylic composite material of the present application comprises:
[0039] The synthesis method of the lacquer acrylic composite material of the present application comprises: mixing lacquer or urushiol, aldehyde substance, catalyst and solvent according to the formula amount at normal temperature, polymerizing for 0.1-4 hours at 60-80℃, and dehydrating by heating to 138℃; after cooling to room temperature, adding acrylic resin and crosslinking agent and reacting for 0.1-0.5 hours; stirring and adding thickening agent for 0.1-0.5 hours, and then obtaining the product.
[0040] The synthesis method of the lacquer acrylic composite material of the present application comprises: the lacquer is refined lacquer, and the acrylic resin is water-based acrylic resin; the method comprises: mixing the refined lacquer, water-based acrylic resin and crosslinking agent, heating to 30-60℃ under nitrogen protection, stirring and reacting for 0.1-2 hours, and cooling to room temperature, and then adding solvent and thickening agent.
[0041] The heating rate during mixing is 5℃ / min, and the nitrogen flow rate is 1-3 bubbles per second.
[0042] In a specific scheme, according to the above mass ratio formula, urushiol, formaldehyde and catalyst are mixed, heated to 70℃ at a heating rate of 5℃ / min, and reacted for 2 hours at a stirring rate of 100r / min; heated to 136℃ for dehydration, cooled to room temperature at a cooling rate of 3-5℃ / min, added with acrylic acid and tung oil resin, and continuously reacted for 0.5 hours; added with hydroxymethyl cellulose modified acrylic copolymer, and dispersed for 20 minutes at room temperature.
[0043] In a specific scheme, according to the above mass ratio formula, urushiol, formaldehyde, dimethylbenzene and ammonia water are mixed, heated to 70℃ under nitrogen protection, and reacted for 2 hours at a stirring rate of 100r / min; heated to 136℃ for dehydration, cooled to room temperature, added with epoxy modified acrylic resin and tung oil, and continuously reacted for 1 hour; added with hydroxyethyl cellulose, and dispersed for 20 minutes at room temperature.
[0044] In a specific scheme, according to the above mass ratio formula, refined lacquer, water-based acrylic resin and tung oil are mixed, heated to 50℃ under nitrogen protection, and reacted for 1 hour at a stirring rate of 100r / min; cooled to room temperature at a cooling rate of 3℃ / min, uniformly stirred with ethyl acetate, added with hydroxyethyl cellulose under high-speed stirring, kept the temperature unchanged, and stirred for 30 minutes.
[0045] The present application also provides a preparation method of the above lacquer acrylic resin composite material, and the specific steps are as follows:
[0046] 1. Raw material pretreatment: raw lacquer is filtered to extract urushiol or remove impurities; acrylic resin is appropriately crushed or dissolved as needed for pretreatment.
[0047] 2. Preparation of mixed solvent: according to the ratio, selected solvents are added to a closed reaction container and stirred uniformly.
[0048] 3. During the synthesis reaction, raw lacquer or urushiol, aldehyde compound, and catalyst are added under stirring, the temperature is raised to 60-80℃, and the reaction is carried out for 2-3 hours, so that the phenolic hydroxyl group and the aldehyde compound fully react and reach crosslinking viscosity, and then the temperature is raised for dehydration.
[0049] 4. Under stirring, the pretreated acrylic resin and chain extender are slowly added, and the reaction is continuously stirred for 10-60 minutes until a certain viscosity is reached.
[0050] 5. During the synthesis reaction, raw lacquer or refined raw lacquer, water-based acrylic resin, and chain extender are heated to 30-60℃ under nitrogen protection, and the reaction is carried out for 0.1-2 hours under stirring; the temperature is lowered to room temperature, and the solvent is added and stirred uniformly.
[0051] 6. Addition of thickening agent: the thickening agent is slowly added to the above-mentioned mixed solution, and high-speed dispersion is carried out for 20-40 minutes to fully disperse the thickening agent and obtain a suitable use viscosity.
[0052] 7. After the reaction is completed, filtration is carried out to remove possible insoluble substances or impurities, and raw lacquer-acrylic resin composite material is obtained.
[0053] The raw lacquer-acrylic resin composite material of the present application is used for preparing functional coatings.
[0054] In combination Figures 1-3 , the acrylic resin of the present application refers to a binary copolymer composed of about 60%-70% of ethyl methacrylate (EMA) and 30%-40% of methyl acrylate. In the present application, the main film-forming substance of raw lacquer, urushiol, can occur condensation reaction with the functional groups such as carboxyl and amide contained in the acrylic resin to form new aryl C-O- bonds; the unsaturated double bond of the side chain of urushiol can occur condensation reaction with the double bond in the acrylic resin molecule. The lacquer film of the raw lacquer-acrylic resin composite material of the present application is tested by infrared, and due to the condensation reaction of phenolic hydroxyl group, the absorption of the association peak of phenolic hydroxyl group at 3400cm-1 is weakened, the absorption peak of C=O bond at 1725cm-1 is enhanced, and the stretching vibration of aliphatic ether C-O at 1151cm-1; the addition reaction of the side chain of urushiol and the side chain of acrylic ester occurs, and the stretching vibration of C=C of the side chain of urushiol is weakened to form a crosslinked macromolecular network system. From the infrared spectrum, it can be seen that condensation and addition reactions occur between raw lacquer and acrylic resin, and the infrared spectrum has obvious changes. -1
[0055] In combination Figure 4 and 5 The lacquer-acrylic resin of the present application can be clearly seen from the surface of the material morphology that the lacquer and the acrylic resin crosslink to form a dense surface morphology, the microporous structure of the lacquer is obviously changed, and the lacquer film has the microporous morphology of the lacquer and the dense network structure of the acrylic resin.
[0056] The acrylic resin has excellent weather resistance and chemical resistance, high gloss, strong adhesion and other characteristics, and is not easily affected by ultraviolet rays and temperature to age and yellow, and the surface is bright after film formation. The acrylic resin has deficiencies in high temperature resistance and solvent resistance, and therefore the present application generates a lacquer-acrylic resin with the durability and chemical resistance of lacquer by chemical reaction of lacquer and acrylic resin, and improves the high temperature resistance, solvent resistance and flexibility of the acrylic resin. In order to further improve the performance of the material, the present application also selects a modified acrylic resin, which has the excellent performance of lacquer and acrylic resin, and has high adhesion, corrosion resistance, flexibility, wear resistance, excellent high temperature resistance (up to 200℃ or more), weather resistance and hydrophobicity, and strong ultraviolet aging resistance. The present application uses various modified resins to prepare a lacquer-acrylic resin with excellent comprehensive performance.
[0057] Example 1: (The molecular weight of the acrylic resin used in this example is 80000)
[0058] The weight percentage formula of the lacquer-acrylic resin of this example is as follows, and the lacquer-acrylic resin prepared by this scheme can be surface dried within 20 minutes. The indexes of the lacquer used in this example are as follows: the lacquer used in this example is a lacquer with a lacquer phenol content of 57% extracted by xylene, and the lacquer phenol content is 65% in Ankang Pingli Jianpan, Shaanxi.
[0059] Component Name Weight Percent (%) Urushiol 30 Formaldehyde 5 Ammonia 2 Acrylic resin 10 Boiled tung oil 5 Hydroxymethyl cellulose modified acrylic copolymer 1 Xylene 47
[0060] According to the above mass ratio formula, the measured lacquer phenol, xylene, formaldehyde and ammonia water are added to a flask, heated to 70℃ at a heating rate of 5℃ / min, and reacted for 2 hours at a stirring rate of 100r / min; heated to 136℃ for dehydration; cooled to 50℃, added with acrylic resin and tung oil, and continued to react for 30min; cooled to room temperature at a cooling rate of 3℃ / min, and added with hydroxyethyl cellulose under high-speed stirring at room temperature, and stirred for 20min.
[0061] Example 2: (The molecular weight of the epoxy-modified acrylic resin used in this example is 10000)
[0062] The weight percentage formula of the raw lacquer acrylic resin of the present application is as follows, and the raw lacquer acrylic resin prepared according to the formula can be surface dried within 20 minutes. The indexes of the raw lacquer used in the present embodiment are as follows: the raw lacquer with a frying disc score of 65% and a urushiol content of 57% in Ankang, Shaanxi, and the urushiol solution extracted by using xylene:
[0063] Component Name Weight Percent (%) Urushiol 30 Formaldehyde 5 Ammonia 2 Epoxy modified acrylic resin 13 Boiled tung oil 5 Xylene 44 Polyamide wax 1
[0064] According to the above mass ratio formula, the measured urushiol, xylene, formaldehyde and ammonia water are added into a flask, heated to 70°C at a heating rate of 5°C / min, and reacted for 2 hours at a stirring rate of 100 r / min; heated to 136°C for dehydration; cooled to 50°C, and then the epoxy modified acrylic resin and the tung oil are added and continuously reacted for 20 min; cooled to room temperature at a cooling rate of 3°C / min, and then the hydroxyethyl cellulose is added under high-speed stirring at room temperature and stirred for 20 min.
[0065] Example 3: (The molecular weight of the water-based acrylic resin used in the present embodiment is 100000)
[0066] The weight percentage formula of the raw lacquer acrylic resin of the present embodiment is as follows, and the raw lacquer acrylic resin prepared according to the formula can be surface dried within 50 minutes.
[0067] Component Name Weight Percent (%) Raw lacquer 30 Waterborne acrylic resin 30 Boiled tung oil 10 Ethyl acetate 29 Hydroxyethyl cellulose 1
[0068] According to the above mass ratio formula, the raw lacquer, water-based acrylic resin and tung oil are heated to 50°C at a nitrogen flow rate of 5 mL / min, and reacted for 1 hour at a stirring rate of 100 r / min; cooled to room temperature at a cooling rate of 3°C / min, and then the ethyl acetate is added and stirred uniformly, and then the hydroxyethyl cellulose is added under high-speed stirring, and the temperature is kept unchanged and stirred for 30 min.
[0069] Example 4: (The molecular weight of the water-based acrylic resin used in the present embodiment is 100000)
[0070] The weight percentage formula of the raw lacquer acrylic resin of the present embodiment is as follows, and the raw lacquer acrylic resin prepared according to the formula can be surface dried within 40 minutes. The indexes of the refined raw lacquer used in the present embodiment are as follows: the frying disc score is 96%, and the urushiol content is 80%.
[0071] Component Name Weight Percent (%) Refined raw lacquer 30 Ethyl acetate 29 Waterborne acrylic resin 30 Boiled tung oil 10 Bentonite 1
[0072] According to the above quality ratio formula, refined raw lacquer, water-based acrylic resin, boiled tung oil, and nitrogen gas flow rate of 10 mL / min were heated to 50℃, and reacted for 1 hour at a stirring rate of 100 r / min. The temperature was lowered to room temperature at a rate of 3℃ / min, and then ethyl acetate was added and stirred uniformly. Hydroxyethyl cellulose was added at a high stirring speed, and the temperature was kept unchanged for 30 minutes.
[0073] The raw lacquer acrylic resin prepared in the above examples can be used according to the general paint use method, and is naturally cured and dried. The paint film has a light color, high hardness, good adhesion, and excellent yellowing resistance, and is a new type of bio-based coating product.
[0074] The raw lacquer acrylic resin has the comprehensive properties of raw lacquer acrylic resin. The basic technical properties of the resin prepared according to the examples are shown in Table 1.
[0075] Table 1: Performance index of raw lacquer acrylic resin
[0076]
[0077]
[0078] The above is only a specific embodiment of the present application, but the present application is not limited to the above embodiment. Various modifications, improvements, and changes of the present application should be included in the protection scope of the present application without departing from the design concept and principles of the present application.
Claims
1. A raw lacquer acrylic composite material, characterized in that, The composite material, by weight percentage, comprises: 5%–30% raw lacquer or urushiol, 1%–2% catalyst, 1%–10% aldehyde, 10%–20% crosslinking agent, 10%–30% acrylic resin, 25%–70% solvent, and 1%–5% thickener; The sum of the percentages of the above raw materials is 100%; The acrylic resin is selected from at least one of epoxy-modified acrylic resin, polyurethane-modified acrylic resin, silicone-modified acrylic resin, and waterborne acrylic resin. The molecular weights of epoxy-modified acrylic resin, polyurethane-modified acrylic resin, and silicone-modified acrylic resin are 5000–10000, 30000–50000, and 20000–50000, respectively.
2. The acrylic composite material for raw lacquer according to claim 1, characterized in that, The acrylic resin is a water-based acrylic resin with a molecular weight of 80,000 to 100,000, and the raw lacquer is refined raw lacquer. The composite material comprises: 5%–30% refined raw lacquer, 10%–20% crosslinking agent, 10%–30% water-based acrylic resin, 25%–70% solvent, and 1%–5% thickener, wherein the sum of the percentages of the above raw materials is 100%.
3. The acrylic composite material for raw lacquer according to claim 1 or 2, characterized in that, The raw lacquer has a lacquer content of over 60% and an urushiol content of over 50%.
4. The lacquer acrylic composite material according to claim 1 or 2, characterized in that, The lacquer mentioned is refined lacquer, with a lacquer content of over 90% and an urushiol content of over 50%.
5. The acrylic composite material for raw lacquer according to claim 1 or 2, characterized in that, The crosslinking agent is at least one of epoxy resin, boiled tung oil, and phthalic anhydride; The thickener is at least one of the following: hydroxymethyl cellulose-modified acrylic copolymer, bentonite, polyamide wax, and hydrogenated castor oil; The solvent is at least one selected from acetone, butanone, ethanol, ethyl acetate, and xylene.
6. The acrylic composite material for raw lacquer according to claim 1, characterized in that, The catalyst is at least one selected from ammonia, ethylenediamine, sodium hydroxide, triethanolamine, benzoyl peroxide, di-tert-butyl peroxide, and methyl ethyl ketone peroxide. The aldehydes mentioned are at least one of formaldehyde, furfural, n-butyraldehyde, and pentylenetetraldehyde.
7. The method for synthesizing the acrylic composite material of raw lacquer according to any one of claims 1-6, characterized in that, include: According to the formula, mix raw lacquer or urushiol, aldehydes, catalyst and solvent at room temperature, polymerize at 60-80℃ for 0.1-4 hours, heat to 138℃ to dehydrate; after cooling to room temperature, add acrylic resin and crosslinking agent and react for 0.1-0.5 hours; stir and add thickener for 0.1-0.5 hours to obtain the final product.
8. The method for synthesizing the acrylic composite material of raw lacquer according to any one of claims 1-6, characterized in that, The lacquer mentioned is refined lacquer, and the acrylic resin is water-based acrylic resin; The process includes: mixing refined raw lacquer, water-based acrylic resin and crosslinking agent, heating with nitrogen gas to 30-60°C, stirring and reacting for 0.1-2 hours; cooling to room temperature, and adding solvent and thickener.
9. The method for synthesizing the acrylic composite material of lacquer according to claim 7 or 8, characterized in that, The heating rate during mixing is 5°C / min; The flow rate of nitrogen gas introduced is 5–10 mL / min.
10. The use of the raw lacquer acrylic composite material according to any one of claims 1-6 in the preparation of functional coatings.